170k views
0 votes
-2(6 - 3n) + 27n = -3(n - 8)

1 Answer

2 votes

We want to solve the following


\text{ -2(6-3n)+27n =-3(n-8)}

First we distribute each multiplication on each side, so we get


\text{ - 12 }+6n+27n=\text{ -3n+24}

If we operate on the left side, we get


\text{ -12 +33n= -3n+24}

Now, we add 3n on both sides, so we get


24\text{ = -12+33n+3n = -12+36n}

Then, we add 12 on both sides, so we get


36n=24+12=36

Finally, we divide boths sides by 36, so we get


n=(36)/(36)=1

So the value of n is 1

User Mehowthe
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.